Effect of problem-solving Skills and gender on emotional stability among students with hearing impairment in Ibadan Oyo State (2021)
This study examined the effect of problem-solving strategy and gender on the emotional stability among students with hearing impairment in Ibadan, Oyo state. The Pretest-posttest control group, quasi experimental design was adopted for the study. Two secondary schools were purposively selected from Ibadan. Thirty-two students with hearing impairment hearing loss were selected for the study. The participants were assigned to experimental and control groups. Those in the treatment group were exposed to problem-solving strategy while those in the control group were not. The treatment lasted eight weeks. The instrument used for data collection was Cattell’s Jr. High School Personality Questionnaire (HSPQ)(r=0.80). Data were analysed using Analysis of Covariance. The hypotheses were tested at 0.05 level of significance. The finding revealed a significant main effect of treatment on emotional stability of the participants (F (1.58=7.532, p<0.05). Gender has no significant main effect on the emotional stability of the participants. There was no interaction effect of treatment and gender on emotional stability of the participants.